2022
DOI: 10.1136/annrheumdis-2021-221865
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of mavrilimumab in giant cell arteritis: a phase 2, randomised, double-blind, placebo-controlled trial

Abstract: ObjectivesGranulocyte-macrophage colony-stimulating factor (GM-CSF) is implicated in pathogenesis of giant cell arteritis. We evaluated the efficacy of the GM-CSF receptor antagonist mavrilimumab in maintaining disease remission.MethodsThis phase 2, double-blind, placebo-controlled trial enrolled patients with biopsy-confirmed or imaging-confirmed giant cell arteritis in 50 centres (North America, Europe, Australia). Active disease within 6 weeks of baseline was required for inclusion. Patients in glucocortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 30 publications
0
36
0
4
Order By: Relevance
“…The most recent work also showed the involvement of processes leading to the amplification and/or maintenance of inflammation and vascular remodeling, such as regulatory T response defects (regulated by IL-6), GM-CSF and the roles of macrophages and NOTCH, along with probably a major role of arterial wall resident cells. These mechanisms identify targets for the development of new therapeutics such as tocilizumab [ 77 ], and more recently, mavrilimumab [ 162 ], secukinumab [ 167 ], JAK inhibitors [ 168 ], abatacept [ 137 ] and ustekinumab [ 169 , 170 , 171 ] ( Figure 3 ) [ 172 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent work also showed the involvement of processes leading to the amplification and/or maintenance of inflammation and vascular remodeling, such as regulatory T response defects (regulated by IL-6), GM-CSF and the roles of macrophages and NOTCH, along with probably a major role of arterial wall resident cells. These mechanisms identify targets for the development of new therapeutics such as tocilizumab [ 77 ], and more recently, mavrilimumab [ 162 ], secukinumab [ 167 ], JAK inhibitors [ 168 ], abatacept [ 137 ] and ustekinumab [ 169 , 170 , 171 ] ( Figure 3 ) [ 172 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a model of an ex vivo culture of temporal arteries treated with GM-CSF or anti-GM-CSF (mavrilimumab), researchers showed that GM-CSF increased the activation of macrophages (expression of IL-1β, IL-6, TNF-α, CD83 and HLA-DR), Th1 cell polarization, angiogenesis and tissue injury (MMP9/TIMP1 ratio) [ 160 ]. These results led a phase-2, randomized, placebo-controlled therapeutic trial to be conducted, the results of which strongly suggest the efficacy of mavrilimumab, a fully human IgG4 monoclonal antibody targeting GM-CSF, in the treatment of GCA [ 162 ].…”
Section: Mechanisms Involved In Maintaining Inflammationmentioning
confidence: 99%
“…Other therapeutic options include inhibition of released cytokines, including IL-17, GM-CSF, and IFN-γ. The efficacy and safety of anti-IL-17 and anti-GM-CSF receptor antibodies against GCA are being actively pursued in clinical trials, and the results obtained to date appear promising ( 100 , 101 ). Signaling downstream of GM-CSF and IFN-γ involves the JAK-STAT pathway, and the efficacy of JAK inhibitors is widely recognized in RA ( 102 ), which raises expectations for the treatment of LVV ( 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, imaging the extent of CD206+ infiltration in the vessels may also predict the GC dependency of these patients. Recently, a phase II clinical trial with a GM-CSF receptor blocker (mavrlimumab) demonstrated GM-CSF receptor blockade to be efficacious in the treatment of GCA ( 390 ). Furthermore, ex vivo treatment of GCA-affected vessels with mavrilimumab documented a reduction of CD206 expression ( 40 ).…”
Section: Future Perspectives: Toward Disease Stratification and Bette...mentioning
confidence: 99%